Embodied Cognition and Alcohol Use Disorder: Frequency of Impairments and Relationship to Neurocognitive Assessments - Morris D. Bell; Andrea J. Weinstein; David Ciosek; Sarah E. Reilly; Yan Wang; Gihyun Yoon (Brain Sciences)
Background: Embodied cognition is an emerging concept in cognitive science that emphasizes the integral role of perception, action, and bodily experience in shaping human thought and understanding. Recently, a new instrument has been developed called the Automated Test of Embodied Cognition (ATEC), which provides a comprehensive measure of eight domains of embodied cognition. Method: An embodied cognition in an alcohol use disorder (AUD) sample (N = 49) was assessed using ATEC, which employs cognitively demanding physical tasks, like an exercise video, to measure executive functions (EFs), memory, and other cognitive processes “in action”. Results: Embodied delayed recall was the most frequent impairment (84%), and EF impairments were also common. Among the EF domains, self-regulation was the most frequently impaired at 43%. Using the ATEC total score, 43% of the sample were rated as having a mild or greater level of overall impairment. Strong support for concurrent validity was found for ATEC EF and memory domains when correlated with neurocognitive assessments conceptually related to them. Significant categorical agreement (impaired/not impaired) was also found between neurocognitive testing and ATEC total score. Using the ATEC total score, younger age, higher education, and better premorbid IQ were found to be potential protective factors against cognitive decline. Conclusions: Findings support ATEC’s potential for future studies related to AUD and other disorders that may lead to cognitive decline. Embodied cognition may provide new insights into how AUD affects cognition and functioning and be useful to determine what interventions may improve recovery.